2018
DOI: 10.1186/s12884-018-2066-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening of differentially expressed proteins from syncytiotrophoblast for severe early-onset preeclampsia in women with gestational diabetes mellitus using tandem mass tag quantitative proteomics

Abstract: BackgroundPrevious studies have revealed that women with gestational diabetes mellitus (GDM) have an increased risk of developing preeclampsia (PE). The possible reason is the abnormal lipid metabolism caused by GDM that leads to dysfunction of vascular endothelial cells and atherosclerosis, resulting in the onset of PE. However, studies focusing on the pathogenesis of PE in syncytiotrophoblast of GDM patients are lacking. This study aimed to compare differentially expressed proteins from syncytiotrophoblast b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…GDM itself is a risk factor for PE and viceversa 25 29 . However, the relationship between pro-/anti-angiogenic factors and PE in women with GDM has been poorly explored 30 32 . From a physiopathological point of view, we expected GDM-PE to behave similarly to PE.…”
Section: Introductionmentioning
confidence: 99%
“…GDM itself is a risk factor for PE and viceversa 25 29 . However, the relationship between pro-/anti-angiogenic factors and PE in women with GDM has been poorly explored 30 32 . From a physiopathological point of view, we expected GDM-PE to behave similarly to PE.…”
Section: Introductionmentioning
confidence: 99%
“…Further functional analysis suggested that GDM is caused by oxidative stress, cell migration, angiogenic disorder, etc. [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, two studies are aimed at investigating adverse fetal outcomes, which selected GDM with macrosomia [33] or GDM with childhood obesity [35] as disease groups. Another study intended to identify biomarkers for one of the GDM-associated complications (early-onset PE) [40], which selected GDM as control groups. Additionally, one study is aimed at comparing GDM with NGT in obese pregnant women [43].…”
Section: Summary Of Proteomic Studies Of Gdmmentioning
confidence: 99%
“…GDM is a complex complication affecting both maternal and fetal health. Several studies used specimens associated with fetomaternal communication, such as placental tissue (villi) [28,36], syncytiotrophoblast [40], and umbilical venous plasma [33,35,39,44]. These samples could provide key proteins for understanding the pathogenesis and progression of GDM, especially for GDM-related maternal complications and adverse fetal outcomes.…”
Section: Summary Of Proteomic Studies Of Gdmmentioning
confidence: 99%
See 1 more Smart Citation